HIV-associated cognitive disorders in children and adolescents: methodological investigations and validating a quick screening tool - Phillips, Nicole Justine (Department of Psychiatry and Mental Health, 2023)
Background Perinatal HIV-infection is associated with both cognitive and functional impairment. Accurate measurement and screening for these conditions is key in ensuring that these vulnerable children and adolescent receive the care they need. Objectives I sought to carry out the following: 1) to undertake a systematic review to determine the cognitive effects of living with HIV in children and adolescents, 2) to determine a statistically sound method for assessing cognitive impairment, 3) to determine the association between cognitive impairment and measures of functional impairment and the relative risk of having functional impairment in the presence of cognitive impairment and 4) to validate a quick screening tool for risk of cognitive impairment in children and adolescents living with HIV. Methods This study was nested within a larger longitudinal study, titled, the Cape Town Adolescent Antiretroviral Cohort (CTAAC). This study is a quantitative cross-sectional study. Each aim led to a study using appropriate methodology. For aim 1; electronic systematic searches where conducted to find relevant literature, which were then assessed by two independent reviewers, data were extracted and then meta-analysed. For aims 2-4; data was collected from research participants enrolled into the CTAAC study. Data scoring, capturing and inferential statistics were conducted in SPSS 25. Results With regards to aim 1, I found that there are both consistencies and inconsistencies in the literature regarding which cognitive domains are most affected by HIV. Findings from the meta-analysis showed that the cognitive domains of executive function, processing speed and working memory are the most affected. With regards to aim 2, I demonstrated statically, that composite cognitive domains scores (as opposed to global scores), were more accurate in detecting HIV-related cognitive differences in adolescents. With regards to aim 3; I found that the functional impairment was strongly and significantly associated with degree of cognitive impairment and that adolescents had an increased risk of having functional impairment if they had cognitive impairment. With regards to aim 4; I demonstrated the statistical validity of the youth International HIV Dementia Scale (y-IHDS) to screen for risk of cognitive impairment in HIV-infected adolescents. The y-IHDS displayed high sensitivity and both positive and negative predictive values for screening for all forms of cognitive impairment. Conclusion Assessment of cognitive and functional impairment in HIV-infected children and adolescents requires special considerations. Methods need to be child/adolescent and time sensitive, and should be contextually appropriate. The methodological approaches and screening tool validated here are a start in addressing these kinds of issues both locally and globally. Neurocognitive disorders are common and can cause clinically significant functional impairment, they are however underrecognized in busy clinical settings. The screening adapted and validated here is an easy to use, quick tool which should be rolled out as part of routine care for all children and adolescents attending antiretroviral (ARV) clinics.